IMPLEMENTASI KOMUNIKASI EFEKTIF DALAM PENGISIAN GENERAL CONSENT DI TPP RSUD KABUPATEN JOMBANG - Soraya Soraya; Hafiz Nayotama; Tri Murni (JRMIK, 2023)
Background: Effective communication is a communication that is able to produce attitude change in the people involvedin the communication. General Consent sheet is a consent sheet given to the patient or family after receiving a completeexplanation from the registration officer.Objective : The purpose of this study was to find out whether the officers at the Patient Registration Center had appliedeffective communication in explaining the content and purpose of the General Consent to patients.Methods : This type of research used a descriptive method with a quantitative approach. Researchers used data collectiontechniques with questionnaires which were distributed to 68 patients and 4 officers at TPP Jombang District Hospital.Results : The level of understanding of officers about the SOP for filling in General Consent only has a percentage of25%. The level of patient understanding of filling out the General Consent. related to filling in the Name on the GeneralConsent sheet has a percentage of 97%, filling in Medical Record Number Medical Record has a percentage of 88.2%,filling out a statement for payment has a percentage of 90%, filling in locqtion, date and time has a percentage of 85%,filling in a signature and clear name has a percentage of 88%, filling in the witness's signature has a percentage of 88%and finally the signature of witnesses from the patient's family has a percentage of 97%. The implementation of effectivecommunication between officers and patients in filling out General Consent was apparently has not optimal and onlyhad an average score below 50.Conclusion : From the results of the study, the researchers found that effective communication between staff andpatients at the TPP RSUD Jombang Regency had not been implemented properly. delivery of information or thoughtsregarding the patient's condition, medical and non-medical actions, treatment plans and the patient's rights andobligations while being treated or carrying out an examination at the hospital.